Aspectos emocionais da experiência do parto - Barros, Marília Vidal de Vasconcelos (Universidade Federal de São Carlos, 2023)
The puerperal pregnancy cycle marks a period of intense changes in the woman's psyche and body, filled with particular emotional demands. Childbirth is an emotionally relevant event, which, depending on its consequences, can significantly impact maternal mental health. The aim of the study is to understand, from the maternal perspective, how the experience of childbirth took place and the thoughts, feelings and emotions involved in this process. To this end, 6 women, recruited in the third trimester of pregnancy, took role in the study. Participants answered a characterization questionnaire, two semi-structured interviews (prenatal and postnatal), the Childbirth Violence Assessment Questionnaire and the Edinburgh Postpartum Depression Scale (EPDS). Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using Interpretive Phenomenological Analysis (IPA). Four of the six interviewees experienced some type of violence during childbirth and two had scores that suggest more intense distress symptoms. The analysis of childbirth reports highlights the diversity of perceptions and emotions in relation to pregnancy and childbirth. The study also emphasized the importance of expectations and the perception of control for the women involved, and the importance of a positive relationship between mothers and health professionals in shaping a positive childbirth experience.
Emotional aspects of childbirth experience
Keywords: Parto; Estados emocionais; Violência contra mulher; Humanização da assistência; Depressão pós-parto; Childbirth; Emotional states; Violence against women; Humanization of care; Postpartum depression; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA